Trading Places : Accessing land in African cities - Napier, Mark.; Project Muse. (Cape Town : African Minds for Urban LandMark, 2013)
Trading Places is about urban land markets in African cities. It explores how local practice, land governance and markets interact to shape the ways that people at society's margins access land to build their livelihoods. The authors argue that the problem is not with markets per se, but in the unequal ways in which market access is structured. They make the case for more equal access to urban land markets, not only for ethical reasons, but because it makes economic sense for growing cities and towns. If we are to have any chance of understanding and intervening in predominantly poor and very.
How the model cracksA mismatch between governance and impact; Two strands of intervention; A new agenda for urban land governance reform; Chapter 5 -- Choices and decisions: Locating the poor in urban land markets; The consequences of unequal land markets; Towards an equitable urban land development agenda; Shifts in development debates; Recommendations for practice; Trading places; Endnotes; References; Acronyms; Glossary; Back cover.
Description based on print version record.
Keywords: Urbanization; Urban poor; Urban policy; Cities and towns -- Growth; SOCIAL SCIENCE -- General; "Museum, historic sites, gallery & art guides."; Urbanisation -- Afrique; Pauvres en milieu urbain -- Afrique; Villes -- Afrique -- Croissance; Politique urbaine -- Afrique; Urbanization -- Africa; Urban poor -- Africa; Cities and towns -- Africa -- Growth; Urban policy -- Africa; Africa; Electronic books